Aplicación de la rt-pcr en tiempo real para el diagnóstico de PRRS - Rubio García, Ana; Rodriguez Prieto, Victor; Kukielka Zunzunegui, Deborah (Revista Complutense de Ciencias Veterinarias, 2007)
PRSS is one of the most important infectious diseases in swine national and international industry because of its economic impact. It is caused by a single stranded RNA virus which its main characteristics are: genetic and antigenic variability, immune modulation properties and its capacity to produce persistent infections. Up to now, there are two main genotypes, the North American (NA) and the European (EU). The comparison of its sequences has shown important genetic differences between them, what contributes to the failure of the existing vaccines against it. One of the most used diagnostic methods is the RT-PCR which complemented with sequencing, leads to determinate the viral genotype. In the last years, new RT-PCRs in real time have been developed because they present advantages as higher sensitivity, quantification of viral load or saving on material and time, improving the control of the disease. In this job, we would like to show the advantages and applications of the real time RT-PCR for the diagnostic and control of the PRRS virus.